2020
DOI: 10.21037/jtd-19-2687
|View full text |Cite
|
Sign up to set email alerts
|

The value of preoperative spirometry testing for predicting postoperative risk in upper abdominal and thoracic surgery assessed using big-data analysis

Abstract: Background:Spirometry is used to evaluate postoperative outcomes in thoracic surgery. However, the clinical utility of spirometry for predicting postoperative complications has not been determined. We used big-data analysis to examine the relationship between pulmonary function tests and postoperative complications. Methods:We retrospectively analysed clinical data from 31,827 patients who underwent spirometry within the 3 months prior to their surgery between January 2000 and December 2014 at a single tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Meanwhile, chronic M. tuberculosis infection has been shown to be an important correlate of poor patient nutritional status and reduced body mass index ( 32 ). In fact, nutritional status in turn has been shown to influence TB disease course and prognosis ( 33 ), which mechanistically may be due to reduced cellular immune function ( 34 ) and hypoalbuminemia in malnourished patients that increase risks of secondary postoperative infections ( 35 ) and respiratory failure ( 36 ). Therefore, improving preoperative nutritional status and correcting preoperative hypoalbuminemia may help to reduce the incidence of postoperative respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, chronic M. tuberculosis infection has been shown to be an important correlate of poor patient nutritional status and reduced body mass index ( 32 ). In fact, nutritional status in turn has been shown to influence TB disease course and prognosis ( 33 ), which mechanistically may be due to reduced cellular immune function ( 34 ) and hypoalbuminemia in malnourished patients that increase risks of secondary postoperative infections ( 35 ) and respiratory failure ( 36 ). Therefore, improving preoperative nutritional status and correcting preoperative hypoalbuminemia may help to reduce the incidence of postoperative respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Park JH et al . [ 33 ] in a critical review concluded that to predict postoperative infection and complications in thoracic and upper abdominal surgery, lower preoperative forced vital capacity values could be used regardless of airflow limitation.…”
Section: Methods Of Pre-anaesthetic Evaluationmentioning
confidence: 99%
“…So far, there is no evidence-based standard protocol for preoperative optimisation of the patient for surgery. [ 33 ] Depending upon the patient’s status, proposed surgery, and available resources, the preparation plan should be tailored for that particular patient. A multidisciplinary approach involving the patient, anaesthesiologist, surgeon, and specialist physician will be helpful.…”
Section: Preoperative Optimisation/prehabilitationmentioning
confidence: 99%
“…In recent years, database-based studies have become popular due to the increase in the size of studies and the number of items to be investigated. Database-based studies are also increasing in the investigation of risk factors for disease [25,26,27,28]. Studies using databases to study breast cancer include studies on treatment selection for breast cancer and epidemiological studies of male breast cancer [29,30], but no studies have used databases to identify risk factors for BCRL.…”
Section: Introductionmentioning
confidence: 99%